THE ANALYSIS OF RESULTS OF SURGICAL TREATMENT OF URINARY INCONTINENCE IN WOMEN: MORPHOLOGICAL ASPECTS - A. L. Neimark; M. V. Razdorskaya; V. Ya. Gervald; V. V. Sharapov; N. S. Shashev (Акушерство, гинекология и репродукция)
Anatomic changes ofparaurethral tissue in women with relapse of urinary incontinence due to stress may testify deficiency or dysplasiaof connective tissue. These may serve as reason of low efficacy of methods with use of own tissues for prolapse correction and urinary incontinence management. These determine the necessity of synthetic materials use.